Implementation of the Altman z-score model in predicting bankruptcy at PT. Garuda Indonesia, Tbk. - Eva Sriwiyanti; Djuli Sjafei Purba; Dendi Wahyudi; Wico Jontarudi Tarigan; Resna Napitu (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: This study aims to forecast Garuda Indonesia’s bankruptcy rate using the Altman Z-Score model analysis tool based on financial statement data for the 2012-2021 period.Design/Methodology/Approach: A quantitative description method was used, with data sources from the Garuda Indonesia website.Research findings: Based on the data analysis, Garuda Indonesia was in a